Sociodemographic, economic, occupational and health perception characteristics which explain the dysfunctional family of informal "sellers" who work of the center of Medellín - Garzón Duque, María Osley; Cardona Arango, María Doris; Rodriguez Ospina, Fabio León; Segura Cardona, Angela María (Universidad y Salud, 2016)
Objective: Identify socio-demographic, economic, occupational and health perception characteristics which explain the dysfunctional family of informal "sellers" who work in the center of Medellín. Materials and methods: A descriptive observational cross-sectional study was performed using primary sources of information to a sample of 170 workers in the year 2009 with a survey that included the SF-36 and the family APGAR. Results: The 35% of those polled presented risk of mild or severe dysfunction family, being less the prevalence for those who were not householders (RP: 0.59.) CI95%: 0,38; 94) and sold drinks – bite and sweet (RP: 0,29. CI-95%: 0.11; 0.77), it was greater for those who perceived less income in the month (Me: $300,000; RQ: 242,000), had fewer dependants (Me: 2; Rq: 2) and belonged to a low socio-economic strata (RP: 2, 82. CI – 95%:1, 40; 5.67). The differences for seven of the eight domains of the SF-36 were observed. Conclusions: The labor and extra labor factors in this working population provide information to the explanation of the prevalence of risk of dysfunctional family, helping to configure their condition of labor vulnerability.